2019
DOI: 10.3390/app9245404
|View full text |Cite
|
Sign up to set email alerts
|

Rolling-Element Bearing Fault Diagnosis Using Advanced Machine Learning-Based Observer

Abstract: Rotating machines represent a class of nonlinear, uncertain, and multiple-degrees-of-freedom systems that are used in various applications. The complexity of the system’s dynamic behavior and uncertainty result in substantial challenges for fault estimation, detection, and identification in rotating machines. To address the aforementioned challenges, this paper proposes a novel technique for fault diagnosis of a rolling-element bearing (REB), founded on a machine-learning-based advanced fuzzy sliding mode obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…The challenge of vibration signal modeling can be addressed by the mathematical-based system modeling five degrees of freedom vibration bearing modeling. Mathematical-based system modeling (such as five degrees of freedom vibration bearing modeling) is reliable but has some drawbacks, such as the lack of complexity and uncertainty related to modeling [ 13 , 14 , 15 ]. Linear-based system identification techniques (such as the combination of autoregressive with external inputs, and autoregressive with external inputs and Laguerre technique) have been used to address the above challenges [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The challenge of vibration signal modeling can be addressed by the mathematical-based system modeling five degrees of freedom vibration bearing modeling. Mathematical-based system modeling (such as five degrees of freedom vibration bearing modeling) is reliable but has some drawbacks, such as the lack of complexity and uncertainty related to modeling [ 13 , 14 , 15 ]. Linear-based system identification techniques (such as the combination of autoregressive with external inputs, and autoregressive with external inputs and Laguerre technique) have been used to address the above challenges [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Related Workmentioning
confidence: 99%
“…The variable structure technique is a robust observer for signal estimation. Based on Equations (13) and (14), and [ 14 ], the state-space equation for variable structure observer is defined using the following equations. …”
Section: Proposed Schemementioning
confidence: 99%
See 1 more Smart Citation
“…Presently, among existing methods, the intelligent signal-based fault diagnosis is considered to be the most popular approach. In this approach, the task of signal-based fault diagnosis is treated as a pattern classification problem, which consists of four main steps: signal acquisition, feature extraction, feature selection, and feature classification [2]. In the first step, signals are measured by different types of sensors attached to the machine.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review of such processing methods can be found in [2][3][4]. More recently, approaches based on machine learning, as those shown in [5], were applied to a vibration dataset in order to identify faulty bearings. Further investigations on such topics regard the enhancement of the fault detection in the presence of noise, as in [6][7][8].…”
Section: Introductionmentioning
confidence: 99%